2020
DOI: 10.3390/microorganisms8030362
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Associated with Rice Phylloplane and Their Contribution to Control of Rice Sheath Blight Disease

Abstract: The phylloplane is an important habitat for yeasts and these yeasts may have antagonistic activities against pathogens and could be used as biocontrol agents. To investigate rice phylloplane yeasts, 282 strains were isolated from 89 rice leaf samples and identified as 15 known yeast species in the phylum Ascomycota and 35 known and two potential new species in the phylum Basidiomycota. The majority of rice phylloplane yeasts belonged to the phylum Basidiomycota. The evaluation of antagonistic activities of 83 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 67 publications
3
22
0
Order By: Relevance
“…The results indicated that only two yeast species, P. laurentii and W. anomalus , were able to solubilize the insoluble form of phosphate (Ca 3 (PO 4 ) 2 ), and zinc (ZnO and ZnCO 3 ). These results were similar to those of other previous studies which reported on the phosphate and zinc-solubilizing abilities of both yeast species [ 26 , 65 , 80 , 81 , 82 ]. Moreover, some species of yeast in the genera Aureobasidium, Barnettozyma, Candida, Holtermanniella, Lachancea, Pichia, Rhodotrula, Saccharomyces, Torulaspora have been recognized for their phosphate and zinc-solubilizing abilities [ 26 , 29 , 80 , 81 , 82 , 83 , 84 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results indicated that only two yeast species, P. laurentii and W. anomalus , were able to solubilize the insoluble form of phosphate (Ca 3 (PO 4 ) 2 ), and zinc (ZnO and ZnCO 3 ). These results were similar to those of other previous studies which reported on the phosphate and zinc-solubilizing abilities of both yeast species [ 26 , 65 , 80 , 81 , 82 ]. Moreover, some species of yeast in the genera Aureobasidium, Barnettozyma, Candida, Holtermanniella, Lachancea, Pichia, Rhodotrula, Saccharomyces, Torulaspora have been recognized for their phosphate and zinc-solubilizing abilities [ 26 , 29 , 80 , 81 , 82 , 83 , 84 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results were similar to those of other previous studies which reported on the phosphate and zinc-solubilizing abilities of both yeast species [ 26 , 65 , 80 , 81 , 82 ]. Moreover, some species of yeast in the genera Aureobasidium, Barnettozyma, Candida, Holtermanniella, Lachancea, Pichia, Rhodotrula, Saccharomyces, Torulaspora have been recognized for their phosphate and zinc-solubilizing abilities [ 26 , 29 , 80 , 81 , 82 , 83 , 84 ]. Additionally, a number of previous studies have reported that the insoluble mineral solubilization ability of yeast cultures can vary depending on the type of mineral and yeast species as well as the particular yeast strain [ 26 , 29 , 83 , 84 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consumers widely accept the development of bio-based applications to exert microbial control in agro-food chains because of the growing demand for eco-friendly approaches and products free of synthetic chemicals [ 78 , 79 , 80 ]. For these purposes, several protective cultures [ 81 , 82 , 83 , 84 ] and compounds of biological origin [ 80 , 85 ] have been assessed for their possible use as Biological Control Agents (BCAs) against B. cinerea in table grapes.…”
Section: Biological Methods To Control B Cinerea mentioning
confidence: 99%
“…However, some concerns have been raised about the effect of synthetic chemicals on human health and the environment as well as pathogen resistance due to the long-term use of chemical fungicide in food crops [ 2 , 3 ]. In the past few years, the biological control of ShB was also reported in several studies by using various microbial antagonists such as Bacillus subtilis strain 916 [ 4 ], Chaetomium aureum strain MF-91 [ 5 ], Trichoderma asperellum [ 6 ] and Phylloplane yeasts [ 7 ].…”
Section: Introductionmentioning
confidence: 99%